The Wisdom Acquired During Emergencies Scale – Development and Validity - Flebus, Giovanni Battista; Tagini, Angela; Minonzio, Marta; Dushku, Eralda; Crippa, Franca (Frontiers in Psychology, 2021)
The COVID-19 pandemic and its related lockdown restrictions had repercussions on health status, psychological states of mind, and emotion regulation. Attitudes towards these restrictions, beliefs, emotions and behaviours could be wise, as in the acceptance of, and adaptation to, these constraints. On the other hand, they could be unwise, as in the rejection of rules and limitations, denial of the consequences, irrational beliefs, self-accusation, rage and general intolerance. This study aims to introduce the development and validation of the 25-item Wisdom Acquired During Emergencies Scale (WADES). It is a measure to assess the wisdom and self-regulation that are needed to cope with unexpected and unpredictable emergency situations. On the basis of a preliminary study (N1=212 Italian adults), a multiple-choice scale of 52 items was developed. In the reliability study (N2=1777), items were scaled, analysed according to the optimal score technique and selected to provide a final and reliable version (Cronbach’s α=0.83). The validity study (N3=1,345, N4=1,445, N5= 878) provided correlations with established scales measuring, for example, traditional wisdom, emotion regulation, empathy, post-traumatic growth, collectivism, conscientiousness and satisfaction with life. The results confirmed that high scores on the WADES are associated with the ability to regulate emotions, control impulses and develop goals in emotional situations, to tolerate current difficulties, while developing new attitudes, values and behaviours, entailing changes in self-perception and relationships. It was thus confirmed that high WADES scores indicate a higher degree of acquired wisdom.